Prognostic and discriminative power of the 7th TNM classification for patients with surgically treated papillary renal cell carcinoma: results of a multi-institutional validation study (CORONA subtype project). (4th July 2017) - May, Matthias; Surcel, Cristian; Capitanio, Umberto; Dell'Oglio, Paolo; Klatte, Tobias; Shariat, Shahrokh; Ecke, Thorsten; Wolff, Ingmar; Vergho, Daniel; Wagener, Nina; Huck, Nina; Pahernik, Sascha; et al.
Abstract: Objective: Studies on the prognostic reliability of the Union for International Cancer Control tumor, node, metastasis (TNM) staging system for renal cell carcinoma (RCC) predominantly focus on clear-cell RCC. Therefore, the aim of this study was to investigate whether the oncological prognosis of surgically treated papillary RCC (papRCC) patients is reliably given by the current TNM system, by analyzing the largest database reported to date. Materials and methods: Data on 2325 papRCC patients who underwent surgical treatment in 1984– 2015 were collated from 17 international centers (median follow-up 47 months). Tumor stage was adapted to the 7th edition of the TNM system. Multivariable, bootstrap-corrected Cox regression models were applied to assess the independent impact of the TNM system on cancer-specific mortality (CSM) and all-cause mortality (ACM). Results: The median age at diagnosis was 63 years (interquartile range 54–70 years) and 77% of patients were male. Nephron-sparing surgery was performed in 42%, and 82% were with symptom free at diagnosis. In 6.7% ( n = 156), organ metastasis (stage M1) was present at the time of surgery. On multivariable analysis, the TNM system and Fuhrman grade had an independent impact on both CSM and ACM, while patient age affected ACM only. The discriminative ability of the pT classification was significant for both endpoints: 5 year CSM rates were 5%, 17%, 36% and 56% for stages pT1, pT2, pT3 and pT4, respectively (each p < 0.001). The pT classification contributed significantly to the predictive accuracy of the CSM and ACM models by 6.3% and 2.5%, respectively (each p < 0.001). Conclusions: The 2010 TNM staging system can be reliably applied to papRCC patients and allows certain prognostic discrimination.